2023
DOI: 10.3390/catal13050913
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic-Based Hydrolysis of Digested Potato Peel Wastes by Amylase Producing Fungi to Improve Biogas Generation

Abstract: Potato peel wastes are generated in high quantities from potato processing industries. They are pollutants to the environment, and they release greenhouse gases into the atmosphere. The present study assessed the potentiality of hydrolyzing potato wastes by amylase-producing fungi to improve biogas generation from potato peels through the anaerobic digestion process. Different fungal isolates were screened for amylase production on potato wastes, and the highest amylase producer was selected for optimizing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…A. oryzae exhibited maximum amylase activity at pH 6 (Balakrishnan et al 2021). Almuhayawi et al (2023) found that amylase activity of Rhizopus stolonifera increased with increasing pH value but the maximum activity was between 4 and 6.…”
Section: Resultsmentioning
confidence: 88%
“…A. oryzae exhibited maximum amylase activity at pH 6 (Balakrishnan et al 2021). Almuhayawi et al (2023) found that amylase activity of Rhizopus stolonifera increased with increasing pH value but the maximum activity was between 4 and 6.…”
Section: Resultsmentioning
confidence: 88%